Particle size and biotic composition on Western Cape shores, including first description of the unique fauna of pebble and cobble beaches - Robbins, Amanda (Department of Biological Sciences, 2021)
Intertidal ecology research has focused primarily on sandy (grain size < 2mm), granule (2 –< 4mm), pebble (4 –< 64mm) or cobble (64 –< 256mm) shores, and only one on the biota of boulder (256+mm) shores. This study samples intermediate shore types (1 – 256mm) within the Western Cape for the first time and compares these with published data on other Western Cape shores to determine how many distinct habitat types occur across the full spectrum of particle sizes with a focus on describing the unique fauna of pebble and cobble shores. Chapter 1 reviews the literature to date on well-studied shore types including sandy and rocky shores, and explores the limited ecological research on shore types ranging from 1 – 256mm, while both data chapters use sample data to complete the study aim. Sampled shores were surveyed using a 20 x 20cm quadrat placed at eight tidal levels along a transect from low to high shore and species collected were identified, counted and wet-weighed. Chapter 2 also used extractions from previously sampled data which included species presence, biomass and abundance per site (where available). All biomass records were converted to wet weight using published conversion factors. Chapter 2 analyzes data from 58 sites in the South-Western Cape, with data for 42 sites derived from eight previous studies, while 16 sites were sampled as part of this study. Three main groupings of sandy shores (1 – 256mm) and boulder and rocky shores (>256mm) occur. Similar to other shores within the spectrum, shores of intermediate particle grain sizes (1 – 256mm) are affected by heavy wave action, among other driving factors. Heavy wave action against intermediate grain sizes which do not have the stability of larger boulders or rocks, or the compacted nature of smaller grain sizes which can be burrowed into to protect biota, results in rough living conditions only few species can endure, as such these shores have a similar biotic composition. A polarization of species presence occurs amongst the two ends of the spectrum with mobile taxa occurring across particle grain size shores between 0.125 – 256mm, but concentrating on smaller grain sizes (256mm. Chapter 3 examines a total of 12 sites in the South-Western Cape, composed of seven pebble and five cobble shores. Of 39 taxa collected on these shores only 14 species occurred more than once and were thus considered typical of pebble and cobble shores. These were mostly air-breathing species, primarily Arthropoda and a single species of pulmonate Gastropoda. Macroalgae were notable in their absence. Unlike the burrowing species of sandy shores, or the attached species of rocky and boulder shores, pebble and cobble shore species all tended to be motile, no doubt to avoid the rolling grains. Unlike most other intertidal shores, the fauna was also concentrated towards the high shore, where food was available in the form of drift kelp, although, as some airbreathing species were found in the low shore, it is presumed some such species migrated well into the intertidal at low tide, presumably retreating back above the high-water mark at high tide.